2010
DOI: 10.4300/jgme-d-09-00078.1
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Systems-Based Competency in Anesthesiology Residency: Development of an Education and Assessment Tool

Abstract: Background The Accreditation Council for Graduate Medical Education requires programs to educate and evaluate residents in 6 competencies, including systems-based practice. We designed a survey and assessment tool to address the competency as it pertains to anesthetic drug costs in an academic center. Methods Residents, certified registered nurse anesthetists, and faculty were asked to complete an anesthetic drug-cost survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Bello et al [ 9 ] demonstrated that the combination of online lecture slides and videos of difficult airway procedures resulted in an increase in postknowledge test scores and positive satisfaction scores. Soto et al [ 17 ] paired didactic online lectures on anesthesia drug costs with “in-person” presentations to improve knowledge scores. Kopp and Smith [ 14 ] showed improved test scores in regional anesthesia with both case-based and traditional textbook style modules.…”
Section: Discussionmentioning
confidence: 99%
“…Bello et al [ 9 ] demonstrated that the combination of online lecture slides and videos of difficult airway procedures resulted in an increase in postknowledge test scores and positive satisfaction scores. Soto et al [ 17 ] paired didactic online lectures on anesthesia drug costs with “in-person” presentations to improve knowledge scores. Kopp and Smith [ 14 ] showed improved test scores in regional anesthesia with both case-based and traditional textbook style modules.…”
Section: Discussionmentioning
confidence: 99%
“…To address these challenges, a number of authors have provided alternative concepts [2] and various methods of teaching and evaluation [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. One internal medicine's residency review committee created education innovations projects to allow certain residency programs to develop new curricula to teach competencies such as SBP [4].…”
Section: Discussionmentioning
confidence: 99%
“…It is important for future clinicians to advocate for their patients and identify health care system deficiencies. Residency programs in all disciplines across the United States have developed specific interventions and curricula to teach SBP and have attempted to evaluate residents in this competency domain [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. To date, however, no long-term analysis of SBP projects within a residency program has been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, in studies that have used more interactive [22] or multi-faceted [23][24][25] educational approaches, improvement in knowledge has been more homogenous among the various knowledge components tested.…”
Section: Discussionmentioning
confidence: 99%